Bio-treatment of poplar via amino acid for interface control in biocomposites. (15th October 2020) - Zhao, Xianhui; Li, Kai; Wang, Yu; Tekinalp, Halil; Richard, Alan; Webb, Erin; Ozcan, Soydan
Abstract: Advanced biocomposites reinforced by abundant biomass-derived fillers can add a revenue stream to enhance the economic viability of biofuel production chains and the energy efficiency of the composite industry. However, the low stiffness of biopolymers limits their use in structural applications. Poplar fibers (mesh size: <180 μm, Populus spp.), an abundant waste from the wood industry, were used as bio-filler to fabricate high-performance biocomposites based on polylactic acid (PLA), in which the poplar fibers were modified by an amino acid (l -lysine). As a benefit of the amino acid treatment, the tensile Young's moduli of the lysine/poplar/PLA composites increased by up to 68% with the addition of a small amount of lysine, compared with neat PLA. At the same time, the tensile strength, failure strain, and Young's modulus of the poplar/PLA composites all increased after adding only 0.1 wt % of lysine. It has been observed that the lysine content has a significant effect on the decomposition temperature, complex viscosity, storage modulus, crystallization temperature, and crystallinity of composites. The fracture surfaces of the composites with an optimum lysine content had fewer voids and were more compact compared with composites without any lysine. The pores on the surfaces of poplar fibers became more available for the penetration of PLA molecules as a result of lysine addition. Therefore, this study presents a facile method for reinforcing biocomposites with extremely low-cost and environmentally friendly biofillers. Graphical abstract: Image 1 Highlights: A small amount of amino acid improved the fiber/PLA interfacial adhesion. Poplar/PLA composites with 0.1 wt% lysine exhibited best tensile strength and modulus. Poplar/PLA composites with 0.1 wt% lysine exhibited superior rheology for 3D printing. A proposed mechanism in composites: chain extension, cross-linking, and degradation.